Shockwaves from Ukraine: Trends and gaps in agricultural commodity prices - Olga Bondarenko (Graduate Institute of International and Development Studies, 2025)
I propose partial-equilibrium models that describe the dynamics of global wheat and corn markets. These models extend the classic competitive storage framework by incorporating nonstationary variables. They are calibrated using data from Ukraine and key importing and exporting countries. The models enable the endogenous estimation of price trends, based on the observed movements in the underlying variables. This framework provides insights into how involuntary reductions in Ukraine's global market presence, triggered by Russia's invasion, could have affected trend prices.
Keywords: C32; C63; Q11; 330; commodity storage; trends; nonstationary models; numerical methods